Blood Acylated Ghrelin Concentrations in Healthy Term Newborns: A Prospective Cohort Study - Neha Parveen; Ayesha Ahmad; Syed Manazir Ali; Shagufta Moin; Nasreen Noor (International Journal of Pediatrics)
Objective. The effect of ghrelin, a growth hormone (GH) secretagogue on growth of neonates, has been studied in the past, but not fully clarified. We aimed to investigate the relationship between ghrelin and growth parameters at birth and at the age of three months in healthy term infants. Methodology. This was a prospective observational study carried out in a tertiary care hospital. Eighty-four infants born at gestational ages between 37 and 42 weeks and classified as term small for gestational age (SGA) and appropriate for gestational age (AGA) were included in the study. Estimation of acylated ghrelin (AG) concentrations was done in the cord blood at birth and in venous blood at the age of 3 months in all the infants. The correlation between AG concentrations and growth parameters at birth and at 3 months was studied. Results. AG concentrations were significantly higher in SGA (236.16±152.4 pg/ml) than AGA neonates (59.45±20.95 pg/ml) at birth. Concentrations were observed to be negatively correlated with birth weight (r=−0.34, p value 0.03), birth length, and head circumference (r=−0.509 and -0.376, respectively) in SGA neonates. However, at 3 months, AG concentrations did not correlate with changes in anthropometric parameters in both the groups. Conclusion. Cord acylated ghrelin concentrations are higher in SGA neonates, and the concentrations are inversely proportional to the birth weight. Hence, its role as a surrogate marker for intrauterine nutrition can be suggested. However, its concentrations do not correlate with anthropometric parameters in early postnatal growth, suggesting it may not have a direct role in postnatal growth.